1992
DOI: 10.1152/ajpgi.1992.262.3.g420
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of [Ca2+]i by secretagogue stimulation of canine gastric parietal cells

Abstract: The ability of gastrin, histamine, and carbachol to stimulate acid secretion by direct action on gastric parietal cells is well established but the role of intracellular Ca2+ concentration ([Ca2+]i) in mediating these effects is the subject of some controversy. To examine this issue further, secretagogue-mediated changes in [Ca2+]i in single isolated canine gastric parietal cells were examined by microspectrofluorometry of fura-2-loaded cells. Resting [Ca2+]i in single parietal cells was 63 +/- 6 (SE) nM. Carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 0 publications
2
37
0
Order By: Relevance
“…This pointed to an electrogenic model of HCOצ secretion such as that elicited by opening of an apical anion conductance. This anion conductance, which seems to transfer Cl¦ as well as notable amounts of HCOצ (the change of alkaline secretion rate corresponded to approximately one-third of the concomitant change in short circuit current), may be activated by a rise in intracellular Ca¥ concentration such as observed after cholinergic stimulation in parietal cells (Chew et al 1992 ;Delvalle et al 1992). Since our observations with pentagastrin resemble very closely those with cholinergic stimulation, we may conclude that pentagastrin also raised intracellular Ca¥ and activated the same apical anion conductance.…”
Section: Mechanism Of Hcoצ Secretion From Ocsmentioning
confidence: 99%
“…This pointed to an electrogenic model of HCOצ secretion such as that elicited by opening of an apical anion conductance. This anion conductance, which seems to transfer Cl¦ as well as notable amounts of HCOצ (the change of alkaline secretion rate corresponded to approximately one-third of the concomitant change in short circuit current), may be activated by a rise in intracellular Ca¥ concentration such as observed after cholinergic stimulation in parietal cells (Chew et al 1992 ;Delvalle et al 1992). Since our observations with pentagastrin resemble very closely those with cholinergic stimulation, we may conclude that pentagastrin also raised intracellular Ca¥ and activated the same apical anion conductance.…”
Section: Mechanism Of Hcoצ Secretion From Ocsmentioning
confidence: 99%
“…Accumulation of inositol 1,4,5-trisphosphate shows biphasic kinetics, with a rapid increase involving a pertussis-toxin-insensitive pathway independent of extracellular Ca2+ and a sustained rise involving a pertussis-toxin-sensitive pathway dependent on extracellular Ca' + [268]. Changes in [Caz+], induced by gastrin stimulation were analyzed on single canine parietal cells [269]. At low gastrin concentrations causing inositol phospholipid breakdown, [Ca'+], oscillations, independent of extracellular Ca" , are detected.…”
Section: Distribution Of the Peripheral Cck Receptorsmentioning
confidence: 99%
“…At low gastrin concentrations causing inositol phospholipid breakdown, [Ca'+], oscillations, independent of extracellular Ca" , are detected. At higher gastrin concentrations, a biphasic rise with an initial transient peak followed by a sustained plateau, is observed [269] [278]. CCK is also believed to regulate contraction and/or relaxation of sphincters including the lower oesophageal sphincter [279], the pylorus [280, …”
Section: Distribution Of the Peripheral Cck Receptorsmentioning
confidence: 99%
“…First, the addition of carbachol, a gastric secretagogue that acts through an increase in [Ca2t]0 (Negulescu & Machen, 1988;Delvalle et al 1992), stimulated the rate of oxoglutarate oxidation (Table 4). This effect was only observed with non-saturating concentrations of oxoglutarate, which is in accordance with the known fact that calcium activates OGDH by lowering the apparent Km for oxoglutarate without altering the Vmax (Denton & McCormack, 1986McCormack, Halestrap & Denton, 1990 (Subero et al 1989) and isolated gastric glands (Hernandez & Chacin, 1994) that showed that carbohydrate oxidation is dependent on calcium concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation by these secretagogues is accompanied by an increase in cytosolic calcium concentration ([Ca2+]e) (Negulescu & Machen, 1988;Delvalle et al 1992). Some recent findings have led to the hypothesis that the increases in [Ca2+]0 could be relayed into the mitochondria, resulting in the activation of several key dehydrogenases, and probably other steps, within the process of oxidative phosphorylation (Hernandez & Chacin, 1994).…”
Section: Introductionmentioning
confidence: 99%